Cost-effectiveness analysis of margin-controlled surgery for vulvar Paget's disease - Kelly H. Bruce; James P. Moriarty; Bijan J. Borah; Ruchita Dholakia; Mary E. Lohman; Jerry D. Brewer; Nahid Y. Vidal; Jamie N. Bakkum-Gamez; William A. Cliby (Elsevier, 2024)
Objectives: To determine the cost of two surgical treatment approaches for vulvar Paget's disease and model the cost-effectiveness considering differences in recurrence and reoperation over time. Methods: We assessed cost-effectiveness between excision guided by Mohs micrographic surgery (MMS-E) and traditional wide local excision (WLE). We examined billing data from patients with vulvar Paget's disease who underwent MMS-E (cases, n = 24, 2018-2022) or WLE (controls, n = 64, 1990-2020). We created typical treatment bundles incorporating physician-administered services and facility costs standardized to Medicare reimbursements in 2022 United States Dollars (USD). The primary measure of effectiveness was disease-free years of life. A secondary analysis estimated quality-adjusted life years (QALY). A Markov model simulated treatment pathways over a 10-year time horizon. Transition probabilities were based on institutional recurrence rates (3-year RR 6.7 % for MMS-E vs 34.1 % for WLE). We used a willingness-to-pay threshold of 100,000 USD per QALY. Results: The cost of a single surgical episode was 34,664 USD for MMS-E and 14,969 USD for WLE. In the setting of lower recurrence rates with MMS-E, the incremental cost was 12,789 USD per disease-free year gained. A secondary analysis incorporating QALY showed an incremental cost of 72,820 USD per QALY. Conclusions: MMS-E appears to be a cost-effective treatment for vulvar Paget's disease compared to historic standard of care. Our ability to estimate quality of life gained by avoiding disease recurrence was limited by scant data for this rare condition; thus, future studies incorporating health utility values are needed to facilitate a more comprehensive analysis.